A coupled surface-subsurface hydrologic model to assess groundwater flood risk spatially and temporally. (April 2019) - Yu, Xuan; Moraetis, Daniel; Nikolaidis, Nikolaos P.; Li, Bailing; Duffy, Christopher; Liu, Bingjun
Abstract: Floods introduced by rainfall events are responsible for tremendous economic and property losses. It is important to delineate flood prone areas to minimize flood damages and make mitigation plans. Recently, there has been recognition of the need to understand the risk from groundwater flooding caused by the emergence of groundwater at the ground surface. Mapping groundwater flood risk is more challenging compared to river flooding, especially in karst systems, where subsurface preferential flowpaths can affect groundwater flow. We developed a coupled surface-subsurface modelling framework resolving spatial information and hydrologic data to assess the groundwater flood risk at a karstic watershed: Koiliaris River Basin, Greece. The simulated groundwater table was used to delineate groundwater flooding. Modelled results revealed the role of faults in groundwater flooding generation. We anticipate the coupled surface-subsurface approach to be a starting point for more sophisticated flooding risk assessment, including magnitude and temporal duration of groundwater flooding. Highlights: Coupled surface-subsurface modelling of a mountainous watershed. Modelling result explicitly shows spatial-temporal dynamics of groundwater flooding. Faults increase the area of groundwater flooding and reduce response time. Groundwater flooding causes more than 10 times higher agricultural loses than river flooding. This study has highlighted the value of coupled hydrologic models in groundwater flooding assessment.